2010
DOI: 10.1093/tropej/fmq084
|View full text |Cite
|
Sign up to set email alerts
|

Hand-touch Method for Detection of Neonatal Hypothermia in Nepal

Abstract: Neonatal hypothermia is the fourth leading causes of neonatal death in Nepal. Thus, it is the caregivers' responsibility to identify the hypothermia by using valid and less time consuming method like hand-touch method. Therefore, we examined the diagnostic validity of hand-touch method against low-reading mercury (LRM) thermometer for detecting neonatal hypothermia. We assessed neonate's temperature first by hand-touch method, then by LRM thermometer and tympanic thermometer among 100 full-term neonates, deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Studies in India and Nepal have shown human touch to be reasonably reliable for the detection of hypothermia when health workers were trained for these investigations. [45][46][47][48][49] Mothers, however, seem to have a far lower sensitivity than health workers. Only 24% of mothers in India were able to correctly identify hypothermia.…”
Section: Diagnosismentioning
confidence: 99%
“…Studies in India and Nepal have shown human touch to be reasonably reliable for the detection of hypothermia when health workers were trained for these investigations. [45][46][47][48][49] Mothers, however, seem to have a far lower sensitivity than health workers. Only 24% of mothers in India were able to correctly identify hypothermia.…”
Section: Diagnosismentioning
confidence: 99%
“…Finally, Tuitui et al 57 conducted a study to examine the diagnostic validity of hand-touch method against axillary mercury thermometer and tympanic thermometer for detecting neonatal hypothermia among 100 full-term neonates, delivered within 24 h in a hospital in Nepal. The sensitivity and specificity of the hand-touch method for detection of neonatal hypothermia were 95.6% and 70.1% against axillary mercury thermometer and 76.6% and 83% against the tympanic thermometer, respectively.…”
Section: A Practical Monitoring Methods To Detect Cold Stressmentioning
confidence: 99%